Magnetic resonance spectroscopy evidence of abnormal cardiac energetics in Xp21 muscular dystrophy. - Crilley, J; Boehm, E; Rajagopalan, B; Blamire, A; Styles, P; Muntoni, F; Hilton-Jones, D; Clarke, K (2000)
OBJECTIVES: Our aim was to measure the cardiac phosphocreatine to adenosine triphosphate ratio (PCr/ATP) noninvasively in patients and carriers of Xp21 muscular dystrophy and to correlate the results with left ventricular (LV) function as measured by echocardiography. BACKGROUND: Duchenne and Becker muscular dystrophy (the Xp21 dystrophies) are associated with the absence or altered expression of dystrophin in cardiac and skeletal muscles. They are frequently complicated by cardiac hypertrophy and dilated cardiomyopathy. The main role of dystrophin is believed to be structural, but it may also be involved in signaling processes. Defects in energy metabolism have been found in skeletal muscle in patients with Xp21 muscular dystrophy. We therefore hypothesized that a defect in energy metabolism may be part of the mechanism leading to the cardiomyopathy of Xp21 muscular dystrophy. METHODS: Thirteen men with Becker muscular dystrophy, 10 female carriers and 23 control subjects were studied using phosphorus-31 magnetic resonance spectroscopy and echocardiography. RESULTS: The PCr/ATP was significantly reduced in patients (1.55+/-0.37) and carriers (1.37+/-0.25) as compared with control subjects (2.44+/-0.33; p<0.0001 for both groups). The PCr/ATP did not correlate with LV ejection fraction or mass index. CONCLUSIONS: Altered expression of dystrophin leads to a reduction in the PCr/ATP. Since this reduction did not correlate with indexes of left ventricular function, this raises the possibility of a direct link between altered dystrophin expression and the development of cardiomyopathy in such patients.